Sustainable water - Ainger, C. M. (Charles M.); Fenner, Richard (Richard A.) (Delivering sustainable infrastructure series, 2016)
Sustainable Water is a practical and accessible book for built environment professionals who play vital roles in creating and maintaining water services. It outlines a framework of fundamental principles, methodologies and approaches needed to deliver high quality, economical and sustainable infrastructure across the globe by approaching it from the time-limited, output-driven perspective of practical infrastructure engineers and practitioners.